Attention‐deficit/hyperactivity disorder and white matter microstructure: The importance of dimensional analyses and sex differences - Scott A. Jones; Bonnie J. Nagel; Joel T. Nigg; Sarah L. Karalunas (Wiley, 2022)
Abstract Background Attention‐deficit/hyperactive disorder (ADHD) has substantial heterogeneity in clinical presentation. A potentially important clue may be variation in brain microstructure. Using fractional anisotropy (FA), previous studies have produced equivocal results in relation to ADHD. This may be due to insufficient consideration of possible sex differences and ADHD's multi‐componential nature. Methods Using whole‐brain analyses, we investigated the association between FA and both ADHD diagnosis and ADHD symptom domains in a well‐characterized, ADHD (n = 234; 32% female youth) and non‐ADHD (n = 177; 52% female youth), case‐control cohort (ages 7-12). Sex‐specific effects were tested. Results No ADHD group differences were found using categorical assessment of ADHD without consideration of moderators. However, dimensional analyses found total symptoms were associated with higher FA in the superior corona radiata. Further, inattention symptoms were associated with higher FA in the corpus callosum and ansa lenticularis, and lower FA in the superior longitudinal fasciculus (SLF), after controlling for overlap with hyperactivity‐impulsivity. Hyperactivity‐impulsivity symptoms were associated with higher FA in the SLF, and lower FA in the superior cerebellar peduncles, after control for overlap with inattention. Meanwhile, both categorical and dimensional analyses revealed ADHD‐by‐sex interactions (voxel‐wise p < .01). Girls with ADHD had higher FA, but boys with ADHD had lower FA (or no effect), compared to their same‐sex peers, in the bilateral anterior corona radiata. Further, higher ADHD symptom severity was associated with higher FA in girls, but lower FA in boys, in the anterior and posterior corona radiata and cerebral peduncles. Conclusions ADHD symptom domains appear to be differentially related to white matter microstructure, highlighting the multi‐componential nature of the disorder. Further, sex differences will be crucial to consider in future studies characterizing ADHD‐related differences in white matter microstructure.